Study on self-management system of urban communities development by base of the biological resources and local wisdom in Prongmadua municipality - Pompranee, Pitakpong (Interdisciplinary Research Review, 2016)
The research aims to study the potential of biological resource and local wisdom on self develop management by using the research combines methods. The results revealed that Prongmadua municipality are semi-urban community and that has self-management system by the use of social capital, biodiversity capital, cultural and local wisdom capital. The important capital resources of the community in the Prongmadua municipality and has led to the integration of leadership for community development as follows: 1) water resources for fish conservation 2) herbal plant in communities 3) public fishing swamp (Som-Seay community) and 4) Prongmadua canal natural sources. The cultural capital and local wisdom were to integrated led to the development community as follows: 1) the cultural heritage of Laos times 2) the master farmers sufficiency 3) the wisdom to make noodles 4) the folk music heritage, youth group 5) the groups of fish communities dribble and 6) the mushroom. The Prongmadua community development in various fields, can be summarized the affect productivity. 4 systems 1) the education system for children and youth. 2) the community economic 3) the community health care system and 4) the knowledge and wisdom.